The Release of Energy During Protein Synthesis at Ultramafic‐Hosted Submarine Hydrothermal Ecosystems. Issue 11 (11th November 2021) - Dick, Jeffrey M.; Shock, Everett L.
Abstract: There are fundamental geochemical reasons why environments surrounding submarine hydrothermal systems are primary productivity hotspots compared with the majority of the seafloor, or with conditions deep in seafloor sediments. As reduced hydrothermal fluids mix with oxidized seawater, elements in incompatible oxidation states are brought together. The resulting rich supplies of disequilibria can be dissipated by primary productivity over wide ranges of temperature and pressure. Synthesis of many amino acids is an energy‐releasing process as fluids from submarine ultramafic‐hosted hydrothermal systems mix with seawater, raising questions about the overall energetics of protein synthesis. Here we show that protein synthesis is also an energy‐releasing process in seawater‐hydrothermal fluid mixtures in ultramafic‐hosted systems, and consider some implications for microbial metabolism, biogeochemical cycles, hydrothermal ecosystem dynamics, and the emergence of life at submarine hydrothermal systems. Plain Language Summary: To grow and reproduce, organisms must synthesize biomass. In oxygenated conditions near Earth's surface, this is an energy‐consuming process. Vastly different conditions prevail at submarine hydrothermal vents, where the mixing of oxygenated seawater with reduced fluids provides chemical disequilibria that sustain thermophilic microbial communities. Thermodynamic calculations for each protein in the genome of a model archeal organism demonstrate the release of energy for protein synthesis from inorganic precursors over a wide temperature range in the mixing zone for fluids from an ultramafic vent but not a basalt‐hosted one. These considerations point to particular submarine hydrothermal systems as hot spots of microbial proliferation for the fundamental reason that biomass synthesis is inherently favored, which is the opposite of the more familiar energetic situation in surface environments. Key Points: Synthesis of proteins is exergonic in the mixing zones of ultramafic‐hosted hydrothermal systems, in contrast to more oxidizing environments The model provides an independent estimate of energetics that depends on amino acid composition but does not capture ATP costs Positive affinities for protein synthesis may contribute to the high abundance of methanogens in ultramafic‐hosted systems